2019
DOI: 10.3389/fpsyt.2019.00063
|View full text |Cite
|
Sign up to set email alerts
|

The Endocannabinoid System and Cannabidiol's Promise for the Treatment of Substance Use Disorder

Abstract: Substance use disorder is characterized by repeated use of a substance, leading to clinically significant distress, making it a serious public health concern. The endocannabinoid system plays an important role in common neurobiological processes underlying substance use disorder, in particular by mediating the rewarding and motivational effects of substances and substance-related cues. In turn, a number of cannabinoid drugs (e.g., rimonabant, nabiximols) have been suggested for potential pharmacological treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 158 publications
1
87
0
2
Order By: Relevance
“…42,43 However, pharmacological intervention is not without risk as has been demonstrated by the adverse psychiatric side effects of Rimonabant, a synthetic CB1 antagonist that was developed to treat obesity, 44,45 and the very serious adverse psychotic effects of the highly potent synthetic cannabinoid agonists colloquially termed ''Spice''. 46 It is perhaps worth noting that some of the most promising medicines targeting eCB signaling are based on using the natural cannabinoids from plants, including D9tetrahydrocannabinol and/or CBD, 47,48 or based on small molecule drugs that increase the levels of AEA 49,50 2-LG IS A PARTIAL AGONIST OF THE CB1 RECEPTOR or 2-AG. 51,52 In this context, strategies that increase 2-LG levels could have therapeutic potential as in some instances, they could introduce or maintain a moderate tone and/or mitigate against overactivation of the system.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 However, pharmacological intervention is not without risk as has been demonstrated by the adverse psychiatric side effects of Rimonabant, a synthetic CB1 antagonist that was developed to treat obesity, 44,45 and the very serious adverse psychotic effects of the highly potent synthetic cannabinoid agonists colloquially termed ''Spice''. 46 It is perhaps worth noting that some of the most promising medicines targeting eCB signaling are based on using the natural cannabinoids from plants, including D9tetrahydrocannabinol and/or CBD, 47,48 or based on small molecule drugs that increase the levels of AEA 49,50 2-LG IS A PARTIAL AGONIST OF THE CB1 RECEPTOR or 2-AG. 51,52 In this context, strategies that increase 2-LG levels could have therapeutic potential as in some instances, they could introduce or maintain a moderate tone and/or mitigate against overactivation of the system.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, studies examining the abuse potential of CBD have not identified any evidence of tolerance or physical dependence [15]. Indeed, some have even suggested that CBD's ability to therapeutically modulate dopaminergic neurotransmission in the mesolimbic pathway supports its role as a treatment for other substance use disorders [70]. Due to these findings, a World Health Organization report recommended that CBD not be labeled as a scheduled substance [15].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Within the eCB system, CBD is a non‐competitive antagonist of CB 1 receptors. CBD acts through negative allosteric modulation and has a low affinity for the primary ligand site of CB 1 receptors (for a recent review, see Chye, Christensen, Solowij, & Yucel, ). The administration of CBD decreases alcohol intake, alcohol‐induced hypothermia, and handling‐induced convulsions without altering blood alcohol concentrations in C57BL/6J mice.…”
Section: The Role Of the Ecb System In Alcohol Intake/self‐administramentioning
confidence: 99%